Tax Debt in the Bankruptcy Dispute: Industries Badja Garuda Inc. v.s. Tax Office of Medan Belawan - Rilda Murniati; Richmond Cosmas Tobias (Rechtsidee, 2018)
The biggest problem for the debtor who is the business actor is his inability to repay the loan to the creditors in case the business activities have problems. The inability to pay may result in the debtor being petitioned for bankruptcy by the creditor or the debtor himself. Curator as the party who performs the management and the settlement of all debtor debts is obliged to make a bill list based on the nature and rights of the bills of creditors as stipulated in Act Number 37 Year 2004 on Bankruptcy and Suspension of Obligation for Payment of Debts (the Law 37/2004). The problem that occurred in the case of Bankruptcy of Industries Badja Garuda Inc. (IBG Inc.) that the Tax Office of Medan Belawan (Tax Office) made a legal effort against the list of tax bills made by the curator of IBG Inc. which set Tax Office as the concurrent creditor through renvoi procedures to the Court Commerce so that the Tax Office loses its precedent over tax debt as stipulated in the Law of Commercial Court refuses the request so that the cassation law is also applied to the Supreme Court which in its decision strengthen the decision of the District Court. For that reason, there is a review effort but the Supreme Court in its sentence Number 45 PK/Pdt.Sus/Pailit/2016 still reinforces the previous verdict. This research is normative research with descriptive type and problem approach applied is normative applied with case study type of court decision. The result of the research indicates that the Tax Office has lost its predecessor right as regulated in Article 21 Paragraph (4) in Act Number 16 Year 2009 regarding General Provisions and Tax Procedures (the Law 16/2009) on the status of tax debt of IBG Inc.